Plasma Kallikrein Cleaved H-kininogen: An End-Point Marker for Contact Activation in vitro and ex vivo - Palarasah, Yaseelan; Pham, Stephanie Thuy Duong; Gram, Jørgen Brodersen; Graversen, Jonas Heilskov; Pilely, Katrine; Sidelmann, Johannes Jakobsen (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objectives: The contact system consists of coagulation factor XII (FXII), prekallikrein, and H-kininogen (HK) and plays important roles in many diseases. Plasma kallikrein (PKa) cleaved HK (cHK) is a marker of contact activation. Presently, we developed a specific and precise enzyme-linked immunosorbent assay (ELISA) for determination of cHK in vitro and ex vivo. Methods: cHK specific mouse monoclonal antibodies (mAbs) were generated using a peptide corresponding to the PKa cleavage site on HK as immunogen. ELISA, surface plasmon resonance analysis, and immunoprecipitation established the specificity of the antibody, which subsequently was used in an ELISA. The analytical imprecision and the concentration of cHK in a reference population and in women receiving oral contraceptives (OCs) were determined. cHK was assessed in vitro in plasma exposed to polytetrafluoroethylene, silicone, and glass tubes. Results: The selected mAb showed excellent specificity towards cHK. The intra-assay and inter-assay CV of the ELISA was 3.6% and 6.0%, respectively. The reference population (60 women, 60 men) displayed a median cHK plasma concentration of 1.38 µg/mL and a reference interval of 0.82 – 2.56 µg/mL. Women receiving OCs had significantly higher concentrations, p <0.001. cHK was significantly elevated in plasma exposed to polytetrafluoroethylene, p=0.001, and glass, p<0.0001. Conclusions: The ELISA showed excellent precision and specificity. cHK assessment ex vivo demonstrated ongoing contact activation in healthy individuals, augmented by OCs. The cHK antibody and the ELISA could be promising tools in contact activation related diseases and in vitro investigations of the plasma compatibility of blood contacting biomaterials.